The emergence of globular clusters and globular-cluster-like dwarfs - Ethan D. Taylor; Justin I. Read; Matthew D. A. Orkney; Stacy Y. Kim; Andrew Pontzen; Oscar Agertz; Martin P. Rey; Eric P. Andersson; Michelle L. M. Collins; Robert M. Yates (Nature, 2025)
Abstract Globular clusters (GCs) are among the oldest and densest stellar systems in the Universe, yet how they form remains a mystery1. Here we present a suite of cosmological simulations in which both dark-matter-free GCs and dark-matter-rich dwarf galaxies naturally emerge in the Standard Cosmology. We show that these objects inhabit distinct locations in the size–luminosity plane and that they have similar ages, age spread, metallicity and metallicity spread to globulars and dwarfs in the nearby Universe. About half of our simulated globulars form by means of regular star formation near the centres of their host dwarf, with the rest forming further out, triggered by mergers. The latter are more tidally isolated and more likely to survive to the present day. Finally, our simulations predict the existence of a new class of object that we call ‘globular-cluster-like dwarfs’ (GCDs). These form from a single, self-quenching, star-formation event in low-mass dark-matter halos at high redshift and have observational properties intermediate between globulars and dwarfs. We identify several dwarfs in our Galaxy, such as Reticulum II (refs. 2–4), that could be in this new class. If so, they promise unprecedented constraints on dark-matter models and new sites to search for metal-free stars.